"We all think boots are meant for men": A community-based participatory assessment of rural women's barriers to preventing podoconiosis in Rwanda. - Gloria Igihozo; Leila Dusabe; Jeanne Uwizeyimana; Esperance Nyiransabimana; Tonya Huston; Janna M Schurer (Public Library of Science (PLoS), 2024)
Podoconiosis is a debilitating neglected tropical disease (NTD) that is possibly caused by prolonged exposure to irritant alkaline clay soil. It is endemic to East Africa and disproportionately affects rural female farmers. The condition can be prevented through foot hygiene and regular wearing of protective shoes. In Rwanda, there is limited information on the factors impacting rural female farmers' access to and utilization of boots while farming. Therefore, this community-based participatory study was conducted to explore the cultural, economic, and ergonomic factors affecting rural farmers' use of protective footwear. Sixteen audio-recorded focus group discussions were conducted with female and male farmers in four villages with the highest podoconiosis prevalence across four provinces of Rwanda. Transcripts were coded inductively using Dedoose (version 9.0.86) and analyzed through thematic content analysis. Participants expressed that wearing shoes protects against diseases and injuries but ability to afford a pair of protective footwear was a major barrier to accessing and wearing them. There were differences in women and men's shoe-wearing behaviors while farming, largely driven by the fact that women who wear boots face rumors and backlash. Findings highlight barriers hindering effective podoconiosis prevention among rural female farmers in Rwanda. Opportunities exist to strengthen podoconiosis and NTD prevention programs, through the integration of gender into existing community-based interventions and the inclusion of local communities into the co-designing of contextualized interventions.